Transport Beyond Oil Policy Choices for a Multimodal Future - Renne, John L.; Fields, Billy (Island Press/Center for Resource Economics : Imprint: Island Press, 2013)
Seventy percent of the oil America uses each year goes to transportation. That means that the national oil addiction and all its consequences, from climate change to disastrous spills to dependence on foreign markets, can be greatly reduced by changing the way we move. In Transport Beyond Oil, leading experts in transportation, planning, development, and policy show how to achieve this fundamental shift. The authors demonstrate that smarter development and land-use decisions, paired with better transportation systems, can slash energy consumption. John Renne calculates how oil can be saved through a future with more transit-oriented development. Petra Todorovitch examines the promise of high-speed rail. Peter Newman imagines a future without oil for car-dependent cities and regions. Additional topics include funding transit, freight transport, and nonmotorized transportation systems. Each chapter provides policy prescriptions and their measurable results. Transport Beyond Oil delivers practical solutions, based on quantitative data. This fact-based approach offers a new vision of transportation that is both transformational and achievable.